Safeguards to Prevent Neurologic Complications After Epidural Steroid Injections: Consensus Opinions From a Multidisciplinary Working Group and National Organizations. Issue 2 (April 2016) - Rathmell, James P.; Benzon, Honorio T.; Dreyfuss, Paul; Huntoon, Marc; Wallace, Mark; Baker, Ray; Riew, K. Daniel; Rosenquist, Richard W.; Aprill, Charles; Rost, Natalia S.; Buvanendran, Asokumar; Kreiner, D. Scott; et al.
Abstract : Surv Anesthesiol 2016;60(2):85–86 Epidural injections of corticosteroids are widely used to treat radicular pain arising from disk herniation or other spinal nerve conditions and are generally associated with only minor adverse effects. There are, however, very rare cases in which injuries to the central nervous system occur as a result of these injections.